Know your price : valuing black lives and property in America's black cities - Perry, Andre M. (Brookings Institution Press, 2020)
"The deliberate devaluation of Blacks and their communities-stemming from America's centuries-old history of slavery, racism, and other state-sanctioned policies like redlining-have tangible, far-reaching, and negative economic and social impacts. Rejecting policies shaped by flawed perspectives, this book gives fresh insights on these impacts and provides a new value paradigm to limit them. Noted educator, journalist, and scholar Andre Perry takes readers on a guided tour of five Black-majority cities whose assets and strengths are undervalued. Perry begins the tour in his hometown of Wilkinsburg, a small city east of Pittsburgh that, unlike its much larger neighbor, is struggling and failing to attract new jobs and industry. Perry gives an overview of Black-majority cities and spotlights four that he has a deep connection to-Detroit, New Orleans, Birmingham, and Washington, D.C.-providing an intimate look at the assets residents should demand greater value from. The book demonstrates through rigorous research and analysis the worth of Black people's intrinsic strengths, real property, and traditional institutions. All of these assets are means of empowerment, as Perry argues for shifting away from simplified notions of equality and moving toward maximizing equity"--